Roles of biochar media and oxygen supply strategies in treatment performance, greenhouse gas emissions, and bacterial community features of subsurface-flow constructed wetlands. (April 2020) - Ji, Bohua; Chen, Jinquan; Mei, Jian; Chang, Junjun; Li, Xuan; Jia, Wei; Qu, Ying
Graphical abstract: Highlights: Biochar was superior to ceramsite for nutrient removal and microbial diversity. Tidal flow enhanced nutrient removal over intermittent aeration. Biochar media and intermittent aeration could reduce greenhouse gas emissions. Operation mode shaped bacterial communities in CWs more than media type. Microbial functions of different CW groups were predicted using Tax4Fun2. Abstract: Biochar-based subsurface-flow constructed wetlands (CWs) with intermittent aeration (IA) or tidal flow (TF) oxygen supply strategies were established to treat domestic wastewater. The results showed that biochar achieved higher nutrient removal and lower greenhouse gas (GHG) emissions than ceramsite while supporting more diverse bacterial communities and higher abundances of functional taxa. Both IA and TF effectively enhanced nutrient removal, though the latter was more efficient and practical, and aeration conditions greatly influenced nutrient removal efficiency. GHG emissions were decreased by IA but were slightly increased by TF. Both oxygen supply methods significantly shaped the biofilm microbial communities and influenced biodiversity and richness, with observably higher proportions of potential nitrifiers and denitrifiers present in aerated CWs. Overall, biochar-based CWs operated with oxygen supply strategies provide superior treatment of decentralized wastewater.